A Study of SERVQUAL Model on Satisfaction and Loyalty of Discharged Dialysis Patients in China - Meng, Lingzhao; Chen, Chenin; Samukkethum, Sujitra (Journal of Social Development and Management Strategy, 2025)
Objective: This study applies the Service Quality Gap (SERVQUAL) model and the inpatient satisfaction questionnaire issued by the National Medical Management Center. It investigates the medical experience and satisfaction levels of discharged dialysis patients. The aim is to provide references for hospitals to enhance service quality. Methods: The study selected 306 dialysis patients discharged from a tertiary hospital in Taiyuan, Shanxi Province, China, between January 2022 and July 2024. Based on the SERVQUAL model, three scales were developed. Questionnaires were distributed online via Questionnaire Star. Statistical software was used for descriptive statistics, reliability and validity tests, correlation analysis, confirmatory factor analysis, and structural equation modeling. Results: Service quality significantly impacts satisfaction. Service quality also significantly impacts loyalty. Satisfaction significantly impacts loyalty. Satisfaction mediates the relationship between service quality and loyalty. Conclusion: Using the SERVQUAL model for satisfaction evaluation helps hospitals identify service weaknesses. It improves patients’ medical experiences and increases satisfaction and loyalty. Additionally, the study suggests strengthening nurse-patient communication and optimizing medical procedures to reduce waiting times, thereby further improving patient satisfaction and loyalty.